Integration of Ethnoscience and Physical Science Perspectives in Determining the Hijri Calendar in Kudus - Hilyana, F. Shoufika; Sumarni, Woro; Handayani, Langlang (Journal of Innovation in Educational and Cultural Research, 2026)
This study explores the integration of ethnoscience and physics perspectives in determining the Hijri calendar in Kudus City, Central Java. Using a qualitative descriptive approach through observation, interviews, and document analysis, this research reveals that the Kudus community harmonizes scientific reasoning (hisab) with empirical and religious practices (rukyat) based on local wisdom. The findings show that the hisab imkan rukyah haqiqi tahqiqi method applied in the Menara Kudus Almanac represents an advanced traditional model that aligns with modern astronomical calculations involving the Moon's synodic cycle, celestial geometry, and atmospheric refraction. Scientifically, this study contributes to understanding how local ethnoscience can complement and contextualize formal knowledge of physics and astronomy. Practically, it provides insights for developing culture-based science education, particularly in astronomy learning, and offers empirical references for policy formulation on Hijri calendar standardization. However, the study is limited to the Kudus context, suggesting the need for comparative research across other Indonesian regions and further validation using digital simulation or optical instrumentation to enrich the integration between local wisdom and scientific astronomy.